Rereading de Man's Readings - Herman Rapaport (Studies in 20th & 21st Century Literature, 1990)
A review article on Reading de Man Reading.
Keywords: Reading de Man Reading; Wlad Godzich; Lindsay Waters; Paul de Man; Geoffrey Hartman; Jacques Derrida; Deborah Esch; Niel Hertz; Carol Jacobs; Peggy Kamuf; Kevin Newmark; J. Hillis Miller; Werner Hamacher; Hans Robert Jauss; Geoffrey Bennington; Bill Readings; Timothy Bahti; Rodolphe Gasché; literary criticism; wartime writings; The Rhetoric of Temporality; literary theory